PERAN ANTIBIOTIKA PROFILAKSIS MENINGITIS PADA FRAKTUR BASIS KRANII - Tjokorda GB Mahadewa*, Sri Maliawan*, AA Raka Sudewi** (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION ONE OF THE MOST COMPLICATION OF SKULL BASE FRACTURE IS CEREBROSPINAL LEACKAGE WHICH CAUSE THE RISK OF MENINGITIS UNTIL 50 THERES STILL CONTROVERSY WEATHER IT NEEDS PROFILAXIS ANTIBIOTICS OR SURGERY TO AVOID THE HAZARD OF MENINGITIS